2017
DOI: 10.1371/journal.pone.0173629
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of Osteopontin in the maintenance of commensal bacteria homeostasis in the intestine

Abstract: Osteopontin (Opn), a multifunctional extracellular matrix protein, is implicated in the pathogenesis of various inflammatory disorders. Under physiologic conditions, its expression is restricted to certain tissues including bone and kidney tubule. However, cellular activation during disease development induces Opn expression in various immune cells. In this study, using Opn-EGFP knock-in (KI) mice we found that CD8α+ T cells in the intestinal tissues, including Peyer’s patch, lamina propria and epithelium, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
0
23
1
Order By: Relevance
“…The phosphoprotein osteopontin, encoded by the gene Spp-1, is a glycosylated molecule that was originally characterized as part of the rat bone matrix [15, 16], and later shown to induce Th1 responses, promote pathogenic Th17 survival, enhance NKT cell activation of concanavalin A-induced hepatitis, and regulate the homeostasis and function of NK cells [1721]. A recent publication shows that lack of osteopontin results in reduced TCRγδ IEL, and that this molecule enhances in vitro survival of TCRαβ and TCRγδ IEL [22]. In steady state conditions, iCD8α cells express significant amounts of osteopontin [11], suggesting a potential role for these cells in IEL homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphoprotein osteopontin, encoded by the gene Spp-1, is a glycosylated molecule that was originally characterized as part of the rat bone matrix [15, 16], and later shown to induce Th1 responses, promote pathogenic Th17 survival, enhance NKT cell activation of concanavalin A-induced hepatitis, and regulate the homeostasis and function of NK cells [1721]. A recent publication shows that lack of osteopontin results in reduced TCRγδ IEL, and that this molecule enhances in vitro survival of TCRαβ and TCRγδ IEL [22]. In steady state conditions, iCD8α cells express significant amounts of osteopontin [11], suggesting a potential role for these cells in IEL homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…2a). To investigate osteopontin production in the IEL compartment, we analyzed Rag-2 −/− mice carrying the Spp-1-EGFP knock-in reporter gene [22]. Whereas NKp46 + NK1.1 + and other CD8α − IEL (NKp46 − NK1.1 lo/− ) presented low GFP staining, most iCD8α cells showed high GFP expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to mention that in order to study innate IEL, our results are based on mice lacking TCR + IEL, and therefore, we do not discard the possibility that some TCR + IEL may be osteopontin producers in wild type mice. Indeed, in steady state conditions, using an osteopontin-GFP reporter system, Hattori’s group showed that TCR + CD8α + IEL represent a source of osteopontin in the intestines of wild type mice [22]. This group also showed that TCRγδ + IEL in vivo are dependent on osteopontin for their survival, whereas in in vitro conditions, both TCRαβ + and γδ + IEL survival is blunted by anti-osteopontin antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, none of the diet interventions led to changes in the gut microbiota composition or diversity, relative to infant formula. Both CGMP and OPN have previously been reported to modulate microbiota composition and play a role in maintaining gut bacterial homeostasis (19,35). In preterm pigs without prenatal inflammation, colostrum feeding also reduced the abundance of Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%